Hirshleifer on Speculation - Salant, Stephen W. (Quarterly Journal of Economics, 1976)
I. Introduction, 667.—II. Do utility deviants speculate? 670.—III. Do concordant beliefs imply a martingale? 673.—IV. The regime of markets, 674.